Pembelajaran Berbasis Gamifikasi Menggunakan Kahoot untuk Meningkatkan Minat Belajar Mahasiswa pada Pembelajaran Online - Marito, Winanda (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to describe gamification-based learning using Kahoot to enhance students' interest in online learning. This study employs a quantitative approach with a quasi-experimental method. The design used is one group pretest-posttest. The sample in this study consists of 30 students from the Physical Education, Health, and Recreation study program. Data collection techniques were conducted through a learning interest questionnaire given before the learning (pretest) and after the learning (posttest) and an observation sheet for the implementation of learning. Data analysis used paired t-test. The research results indicate that there is a 15.5% increase in student learning interest with a t-value of 15.847, p < 0.001, which means there is a significant difference in the increase of student learning interest before and after the implementation of gamification-based learning with Kahoot. The success rate of the learning implementation is 88.75% across all observed aspects, including lesson preparation, execution, student activities, and time management. These findings indicate that gamification-based learning using Kahoot can enhance student learning interest in online learning.